Exploring the experiences, attitudes and knowledge of radiographers and forensic pathologists regarding forensic radiography services in Lagos state, Nigeria - Kekana, R.M. (Mable) (University of Pretoria, 2020)
Dissertation (M.Rad)--University of Pretoria, 2020.